2013
DOI: 10.1038/nsmb.2692
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of allosteric activation of SAMHD1 by dGTP

Abstract: SAMHD1, a deoxyribonucleoside triphosphate triphosphohydrolase (dNTPase), plays a key role in human innate immunity. It inhibits infection of blood cells by retroviruses, including HIV, and prevents the development of the autoinflammatory Aicardi-Goutières syndrome (AGS). The inactive apo-SAMHD1 interconverts between monomers and dimers, and in the presence of dGTP the protein assembles into catalytically active tetramers. Here, we present the crystal structure of the human tetrameric SAMHD1-dGTP complex. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
276
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(304 citation statements)
references
References 38 publications
26
276
2
Order By: Relevance
“…We found that racemic dGTPαS was a very slow substrate in the absence and presence of transactivation by GTP (t 1/2 = 24 h) (Fig. S5), which is consistent with the crystal structure showing that dGTPαS can bind to the A1 and A2 activator sites as well as the catalytic sites (20). Supporting the suggestion that dGTPαS can self-activate, it also served as a weak transactivator for dUTP hydrolysis at low concentrations (K dGTPαS act = 8 ± 2 μM and k dUTP cat = 0:9 ± 0:1 s −1 ) and an inhibitor at higher concentrations ðK dGTPαS i = 67 ± 19 μMÞ (Fig.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…We found that racemic dGTPαS was a very slow substrate in the absence and presence of transactivation by GTP (t 1/2 = 24 h) (Fig. S5), which is consistent with the crystal structure showing that dGTPαS can bind to the A1 and A2 activator sites as well as the catalytic sites (20). Supporting the suggestion that dGTPαS can self-activate, it also served as a weak transactivator for dUTP hydrolysis at low concentrations (K dGTPαS act = 8 ± 2 μM and k dUTP cat = 0:9 ± 0:1 s −1 ) and an inhibitor at higher concentrations ðK dGTPαS i = 67 ± 19 μMÞ (Fig.…”
supporting
confidence: 74%
“…Unlike GTP, dGTP can activate its own hydrolysis and is known to serve as a transactivator for hydrolysis of other substrate dNTPs at low concentrations (17). However, it should also act as an inhibitor of dNTP hydrolysis at higher concentrations (20,22). To explore these properties of dGTP, we determined the concentration dependence of the initial rates of dGTP hydrolysis at an SAMHD1 concentration of 0.2 μM and variable concentrations of dGTP in the range of 5 μM to 5 mM ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations